Shakespeare’s original will: a re-reading, and a reflection on interdisciplinary research within archives - Bevan, Amanda; Foster, David (British Records Association, 2017)
Much academic ink has been spilled on the importance of William Shakespeare’s last will and testament, particularly as a source illuminating his life and character. Drawing upon recent archival research and technical analysis, this article details the processes by which interdisciplinary approaches to the will have resulted in a fundamental reinterpretation of what the contents of the will can tell us about Shakespeare’s final years.